Ανάπτυξη μαθηματικού μοντέλου αναερόβιας χώνευσης ιλύος - Κόκκινος, Ηλίας (Εθνικό Μετσόβιο Πολυτεχνείο--Μεταπτυχιακή Εργασία. Διεπιστημονικό-Διατμηματικό Πρόγραμμα Μεταπτυχιακών Σπουδών (Δ.Π.Μ.Σ.) “Επιστήμη και Τεχνολογία Υδατικών Πόρων”, 2017)
The aim of this diploma thesis is the systematic and detailed analysis of the processes of anaerobic digestion. Specifically, digester analysis is performed in sludge treatment systems while at the same time comparing with data from existing anaerobic digestion units. For this purpose algebraic and differential equations are developed to study the behavior of anaerobic digestion systems in different conditions of HRT (Hydraulic Retention Time), Temperature, pH, as well as a different composition of sludge mixture to be treated. The Matlab programming language was used as a tool, as the required equations are stiff Ordinary Differential Equations and therefore difficult to solve by the small step of Runge-Kutta methods which is the most common methods of solving such systems. The computational part of this paper contains a code of equations, which came from the mathematical model ADM1. This code undergoes multiple modifications to perform different types of analyzes in anaerobic digestion systems. The initial modification involves the incorporation of a model that works as an interface between ASM1 and ADM1, in order to allow total analysis at sewage treatment plants. A sensitivity analysis is then performed to investigate the effect of program constants on the effects of anaerobic digestion. As can be seen from the tables listed above, the sensitivity analysis, coupled with anaerobic digestion data, leads to a change in the values of the ADM1 stables and gives more accurate and realistic conclusions as regards both biogas production and the concentrations of outgoing variables. The results of the generated code are analyzed in algebraic equations, resulting in the creation of a new, easy-to-use and reliable code incorporated in the overall model developed in the research program of the Sanitary Technology Laboratory of the N.T.U.A. This leads to a global simulation, which calculates all the concentrations of parameters, energy requirements and greenhouse gas emissions of a sewage treatment plant. This simulation is applicable to every form and layout of a whole sewage treatment plant.